INPP5E regulates phosphoinositide-dependent cilia transition zone function - Jennifer M. Dyson; Sarah E. Conduit; Sandra J. Feeney; Sandra Hakim; Tia DiTommaso; Alex J. Fulcher; Absorn Sriratana; Georg Ramm; Kristy Horan; Rajendra Gurung; Carol Wicking; Ian Smyth; et al. (2016)
Human ciliopathies, including Joubert syndrome (JBTS), arise from cilia dysfunction. The inositol polyphosphate 5-phosphatase INPP5E localizes to cilia and is mutated in JBTS. Murine Inpp5e ablation is embryonically lethal and recapitulates JBTS, including neural tube defects and polydactyly; however, the underlying defects in cilia signaling and the function of INPP5E at cilia are still emerging. We report Inpp5e−/− embryos exhibit aberrant Hedgehog-dependent patterning with reduced Hedgehog signaling. Using mouse genetics, we show increasing Hedgehog signaling via Smoothened M2 expression rescues some Inpp5e−/− ciliopathy phenotypes and “normalizes” Hedgehog signaling. INPP5E’s phosphoinositide substrates PI(4,5)P2 and PI(3,4,5)P3 accumulated at the transition zone (TZ) in Hedgehog-stimulated Inpp5e−/− cells, which was associated with reduced recruitment of TZ scaffolding proteins and reduced Smoothened levels at cilia. Expression of wild-type, but not 5-phosphatase-dead, INPP5E restored TZ molecular organization and Smoothened accumulation at cilia. Therefore, we identify INPP5E as an essential point of convergence between Hedgehog and phosphoinositide signaling at cilia that maintains TZ function and Hedgehog-dependent embryonic development.